Study of Magnetic Shielding of Ferromagnetic Cores, With Solenoidal HTS Tape Screens, for SFCL Applications - Alfredo Alvarez; Belen Rivera; Belen Perez; Pilar Suarez (IEEE Access)
Superconducting Fault Current Limiters (SFCL) are reliable and low environmental impact protection devices, easily adaptable within the distribution networks of distributed generation systems. An Inductive-resistive (IR) SFCL, previously presented by authors, is currently under development. The inductive stage of this IR-SFCL has a magnetic screen to prevent the magnetic field from affecting the resistive stage during normal operation, among other functions. Usually, the magnetic screens are made of superconducting bulk, and have low reliability under thermal cycles, since they are brittle and expensive. To solve this problem, screens built from commercial high temperature superconducting (HTS) tape were studied and the best configuration for use in the IR-SFCL, chosen. This was the superconducting multilayer solenoidal screen. This work studies the behaviour of the basic IR-SFCL ferromagnetic core, when it is shielded by the chosen superconducting multilayer solenoidal screen. This paper shows the magnetic conditions to prevent or permit the magnetization of the core, which is necessary information to size the inductive stage of the new IR-SFCL prototype. Finally, a brief study of the shielding mechanisms of the new screen was carried out. The result of the tests proves that the diamagnetism of the tape superconducting materials is almost totally responsible for the magnetic shielding.